Effect of microalgal diets and its biochemical composition on growth and survival of Asiatic freshwater clam - Waleewan Changpasert,; Saou-Lien, Wong; Kittikoon Torpol, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Corbicula fluminea clam is one of the most popular food ingredients and nutritional supplements in Taiwan. Increasing the biomass of the clam by culturing it with a proper diet is necessary. For the potential of food availability of the C. fluminea clam, growth and survival were studied by rearing five species of live microalgal diets for eight weeks. The results revealed that the clams fed on C. pyrenoidosa, O. multisporus and C. cryptica showed outstanding results in shell growth and live weight gain. The maximum percentage of clam growth rate, which was measured by shell length, live weight gain and survival rate were found when fed on C. pyrenoidosa, O. multisporus and C. cryptica, respectively. However, the clams had a negative live weight gain when fed on S. acutus and C. microporum, due to the inappropriate size of the diets. The most significant protein content in clam tissue was shown when fed on C. pyrenoidosa (58.34%), and C. cryptica stimulated the highest lipid content in clam tissue (25.06%). Therefore, it suggested that the most suitable live microalgal foods are C. pyrenoidosa, O. multisporus and C. cryptica, for which useful algae and non-toxic species were selected to support C. fluminea growth.